PKM Society Empowering dalam Upaya Pengingkatan Digitalisasi Keuangan Syariah bagi Pondok Pesantren - Rahmat Ilyas; Rudi Hartono; Aswin Aswin (Jurnal Pengabdian UNDIKMA, 2022)
This community service activity aims to provide education and literacy related to the digitalization of Islamic finance for the Madinatul Ilmi Islamic Boarding School in Sangku Teritip Village, West Bangka Regency, Bangka Belitung Island Province. The method used in this service activity is offline training. The evaluation instrument of this service activity used questionnaires and interviews which are then analyzed descriptively. The results of this community service activity show that teachers of Islamic boarding school, staffs, and students of the Madinatul Ilmi Islamic Boarding School have knowledge about the digitalization of Islamic finance and its benefits in growing both micro and macro economic growth. Besides, the result of this activity shows that the clerics have been able to apply digitalization in finance sharia.